Effect of Quarrying Dust on Leaves Weight and Plants Chlorophyll Content of Pawpaw (Carica papaya), Cassava (Manihot esculenta) and Okra (Abelmoschus esculentus) in Akamkpa, Cross River State, Nigeria - E. A. Enoh; P. A. Ogwo; E. A. Ubuoh (Journal of Applied Sciences and Environmental Management, 2023)
Accumulation of dust and other particulate matter on crops could affect photosynthesis, respiration, transpiration and allow the penetration of phytotoxic gaseous pollutants, hence the agricultural crops show stunted growth, minimum leaf area, less number of leaves and block the stomata opening. The objective of this study is to determine the effect of quarrying dust on leaves weight and selected plants chlorophyll content of Pawpaw (Carica papaya), Cassava (Manihot esculenta) and Okra (Abelmoschus esculentus) in Akamkpa, Cross River State, Nigeria using standard methods. The plant species were obtained at distances of 300m, 600m and 900m away from the quarry site. Higher chlorophyll contents were recorded in wet season than in the dry season, with total chlorophyll ranging between 2.25-2.81mg/g, 2.23-2.89mg/g and 1.87-2.24mg/g for Carica papaya, Manihot esculenta and Abelmoschus esculentus respectively in the dry season and then 2.43-3.01mg/g, 2.68-3.19mg/g and 2.16-2.77mg/g for Carica papaya, Manihot esculenta and Abelmoschus esculentus respectively in the wet season. Results of chlorophyll a and b in the sampled plants indicated lower effects of dust on chlorophyll contents of the plant leaves with distance away from the quarry site.